Robotic Construction of Tensegrity Structures - Issa, Margulan (Nazarbayev University School of Science and Technology, 2017)
Tensegrity based design is emerging as an active research field. Tensegrity structures can be constructed with minimal weight compared to the traditional ones. They can also have stability and durability without relying on gravity. These merits make them ideal for the construction of orbital structures such as space stations. Even though the researchers have recently crafted elegant theories for the statics and dynamics of tensegrity, there are many hurdles for their active utilization in space construction. Due to the need for attaching strings in complex geometries and precise tensioning of these, the labor and skill intensive construction of these tensegrities in space cannot be accomplished by humans. With recent advances in robotics especially in embedded computing, sensing and motion planning, robots can be summoned to tackle the automated construction problem of tensegrities. To the best of the author’s knowledge, an automated construction framework for tensegrities does not exist. This thesis focuses on this problem. Firstly, we describe our assembly-friendly tensegrity struts with integrated strings and tensioners. Secondly, we present the development and implementation of a specialized robot end-effector for tensegrity construction. This end-effector with embedded sensors and computation is capable of measuring the string tension based on vibration frequency, attaching/detaching strings and also tensioning them. Using these components, we developed a framework for robotic construction of tensegrity structures. We show the efficacy of our framework by real world experiments. In particular, we constructed a 3-strut and 9-string tensegrity prism which can serve as a building block for more complex structures.
Keywords: Robotic Construction